Towards an understanding of New Zealand Union responses to climate change. (2nd January 2021) - Douglas, Julie; McGhee, Peter
ABSTRACT: The vulnerability and viability of industries due to negative impacts of climate change are clear, and ultimately the future of work will be reshaped. Traditionally unions have focused on wages and conditions but there is an increasing call for unions to be at the core of future decisions regarding the climate change response. This article draws on a two-stage project which explored the views of union leaders on union preparedness to climate change and also a survey of union members on their expectations of their unions to the issue. While there is a high level of concern about climate change there has been a sluggish response from unions and a significant gap between the unions' position and the expressed belief from members that unions need to take an active role on climate change. Members indicated low collective efficacy in their unions to step into leadership roles. We offer several reasons for these findings and suggest ways forward.